Egy unortodox jegybanki adatrevízió háttere, utóélete és tanulságai - Oblath Gábor (Hungarian Academy of Sciences, Institute of Economics, 2017)
– In December 2016 the National Bank of Hungary (NBH), by referring to its "backcasts" (based on analyses of past data-revisions), arbitrarily revised upwards the data of the Hungarian Statistical Office (HSO) on GDP-growth for the first three quarters of 2016. This "methodological innovation" (as put by the NBH) served to support its unrealistic 2.8 percent GDP-growth projection for 2016. In March 2017, the HSO reported GDP to have grown by a mere 2 percent in 2016. Hence, the "backcast" of the NBH, combined with its forecast for the last quarter of 2016, proved to be a failure. However, the NBH did not give up: without offering a substantive explanation for its forecast error, it claimed in its 2017 March Inflation Report that GDP-growth was by 0.2 percentage points higher in 2016 than reported by the HSO. This mode of conduct of the NBH can be objected both on ethical and professional grounds. By this practice the NBH not only questions the reliability of official statistical data, but it also makes its forecasts incomparable both across time and with those of other analysts. While expressing uncertainty regarding future data-revisions by a central bank certainly makes sense, there are no professional arguments to support a practice whereby a central bank simply overwrites official data by its extremely uncertain "backcasts".
Keywords: E01; E37; E58; 330; GDP-statistics and data revisions; macroeconomic analysis; forecasts and backcasts; National Bank of Hungary; central bank transparency